Gene and Protein Expression of Chemokine (C-C-Motif) Ligand 19 is Upregulated in Unstable Carotid Atherosclerotic Plaques. Issue 4 (October 2016) - Salem, M.K.; Butt, H.Z.; Choke, E.; Moore, D.; West, K.; Robinson, T.G.; Sayers, R.D.; Naylor, A.R.; Bown, M.J.
Abstract : Objective/Background: The aim was to investigate the expression of genes associated with carotid plaque instability and their protein products at a local and systemic level. Methods: Carotid plaques from 24 patients undergoing carotid endarterectomy (CEA) were classified as stable or unstable using clinical, histological, ultrasound, and transcranial Doppler criteria, and compared using whole genome microarray chips. Initial results of differentially expressed genes were validated by quantitative reverse transcriptase polymerase chain reaction in an independent group of 96 patients undergoing CEA. The protein product of genes significantly differentially expressed between patients with stable and unstable plaques were analysed by plaque immunohistochemistry and serum protein quantification by enzyme-linked immunosorbent assay on a further independent cohort. Results: Expression of chemokine (c-c-motif) ligand 19 (CCL19) was significantly upregulated in plaques from patients with clinically unstable disease ( p  < .001). Cathepsin G expression was upregulated in histologically unstable plaques ( p  = .04). Serum concentration of CCL19 was significantly higher in patients with clinically unstable plaques ( p  = .02). Immunohistochemical staining for CCL19 demonstrated positive staining in histologically and clinically unstable plaques ( p  = .03). CCL19 also co-localised with CD3 + T-cell lymphocytes in the core region, around where CCL19 was expressed. Conclusions: CCL19 is significantly overexpressed in patients with unstable carotid atherosclerotic plaques and may be a possible novel biomarker for identifying high-risk patients in whom more urgent intervention may be indicated.